A pathological study of Leishmania infantum natural infection in European rabbits (Oryctolagus cuniculus) and Iberian hares (Lepus granatensis). Issue 6 (8th August 2019) - Ortega‐García, María Victoria; Salguero, Francisco J.; Rodríguez‐Bertos, Antonio; Moreno, Inmaculada; García, Nerea; García‐Seco, Teresa; Luz Torre, Gabriela; Domínguez, Lucas; Domínguez, Mercedes
Abstract: In this study, we describe the pathology of Leishmania infantum infection in naturally infected wild Leporidae and compare diagnosis of infection using histopathology, direct fluorescent antibody (DFA) assay, immunofluorescence antibody test (IFAT) and quantitative real‐time PCR (qPCR) . Tissues were analysed from 52 European rabbits ( Oryctolagus cuniculus ) and 7 Iberian hares ( Lepus granatensis ) from the Community of Madrid (Spain). Our results show that L. infantum infection is associated with only minimal histopathological lesions and that L. infantum amastigotes can be detected by DFA assay in all tissues types tested, including skin. These results were confirmed by qPCR on fresh frozen tissues in 13% of rabbits and 100% of hares. However, L. infantum DNA could not be detected by qPCR on paraffin‐embedded tissue obtained by laser capture microdissection. Using the DFA assay to diagnose L. infantum, infection may provide further insights into this disease in wild animals and may allow the precise tissue localization of L. infantum, thereby guiding follow‐up tests with more accurate qPCR.